Mutual Legal Assistance (Mla) In The Resolution of Narcotics Crime As A Transational Organized Crime - I Made Wirya Darma; Ni Nyoman Sri Wisudawati; I Gede Agus Kurniawan (Fakultas Hukum Universitas Udayana, 2020)
In the context of enforcing the law on narcotics crime which are transnational, Indonesia since 2006 has encated Law Number 1 of 2006 on Mutual Legal Assistance in Criminal Matters. Prevention and eradication of various transnational crimes, especially narcotic drugs, a mutual assistance agreement in criminal matters is one of the legal instruments that is needed. Therefore, the presence of bilateral agreements on mutual assistance in criminal matters between Indonesia and other countries will support law enforcement efforts as expected in enforcing the law against transnational narcotics offenders. This study focuses on several indications that become a reference in the handling of narcotics and psychotropic crimes as one of transnational organized crime through the mechanism of Mutual Legal Assistance (MLA). The method used in this study is normative legal research by reviewing and analyzing the provisions of the law governing Mutual Legal Assistance (MLA) in Indonesia, especially against narcotics crime. The results showed that mutual assistance in the problem of narcotics crime as a type of transnational organized crime can be done based on an agreement and in case of the absence of agreement, the assistance is carried out on the basis of good relations.